1995
DOI: 10.1128/jvi.69.11.6980-6993.1995
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a new simian T-cell leukemia virus type 1 from naturally infected celebes macaques (Macaca tonkeana): complete nucleotide sequence and phylogenetic relationship with the Australo-Melanesian human T-cell leukemia virus type 1

Abstract: A study of simian T-cell leukemia virus type 1 (STLV-1) infection in a captive colony of 23 Macaca tonkeana macaques indicated that 17 animals had high human T-cell leukemia virus type 1 (HTLV-1) antibody titers. Genealogical analysis suggested mainly a mother-to-offspring transmission of this STLV-1. Three long-term T-cell lines, established from peripheral blood mononuclear cell cultures from three STLV-1-seropositive monkeys, produced HTLV-1 Gag and Env antigens and retroviral particles. The first complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 78 publications
1
40
0
Order By: Relevance
“…This conclusion is also supported by the fact that these individuals lived in widely separated areas of the western part of Central Africa without any evidence of recent contact. Recent studies (28,42,47,48,65,80) have suggested that the present world repartition of HTLV-1 genotypes is the result of at least three independent events, interspecies transmission of STLV-1 to humans (as in the case of chimpanzees in Central Africa), independent evolution of the virus in some remote areas (as in Melanesia), and migrations of infected populations (as, for example, during the slave trade). We therefore hypothesize that the presently described new HTLV-1 genotype (subtype D) may have taken its origin in interspecies transmission from monkeys to humans in Central Africa and that there exists or existed in Central Africa an STLV-1 closely related to this HTLV-1 subtype D genotype.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This conclusion is also supported by the fact that these individuals lived in widely separated areas of the western part of Central Africa without any evidence of recent contact. Recent studies (28,42,47,48,65,80) have suggested that the present world repartition of HTLV-1 genotypes is the result of at least three independent events, interspecies transmission of STLV-1 to humans (as in the case of chimpanzees in Central Africa), independent evolution of the virus in some remote areas (as in Melanesia), and migrations of infected populations (as, for example, during the slave trade). We therefore hypothesize that the presently described new HTLV-1 genotype (subtype D) may have taken its origin in interspecies transmission from monkeys to humans in Central Africa and that there exists or existed in Central Africa an STLV-1 closely related to this HTLV-1 subtype D genotype.…”
Section: Discussionmentioning
confidence: 99%
“…PCR. PCR was carried out as previously described (25,29,42). Briefly, highmolecular-weight DNA was extracted from PBMCs before or during cell culture by a classical phenol-chloroform technique.…”
Section: Serological Tests For Serum Samples Obtained Through the Pamentioning
confidence: 99%
See 3 more Smart Citations